2003
DOI: 10.1016/s0378-1127(03)00207-x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration after wildfire in communities dominated by Pinus pinaster, an obligate seeder, and in others dominated by Quercus pyrenaica, a typical resprouter

Abstract: The effects of wildfire on vegetation regeneration in communities dominated by Quercus pyrenaica and those dominated by Pinus pinaster in NW Spain were compared. In order to study changes in the composition and structure of both types of community, permanent plots were established in areas dominated by Q. pyrenaica and those dominated by P. pinaster. All were burned by wildfires at the end of summer. In each plot a permanent transect of 20 m  1 m was established. Basal cover of the plant species present was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 36 publications
3
65
1
4
Order By: Relevance
“…7) agreed with the results of previous non-remote sensing-based studies also centered on P. pinaster. In our study area, Calvo et al (2003Calvo et al ( , 2008Calvo et al ( , 2013 concluded that the dominant species, P. pinaster, had a predominantly high rate of natural regeneration. Mean seedling height showed a significant increase in time (5 years) at the study area from 1.7 to 49.5 cm.…”
Section: ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg mentioning
confidence: 69%
“…7) agreed with the results of previous non-remote sensing-based studies also centered on P. pinaster. In our study area, Calvo et al (2003Calvo et al ( , 2008Calvo et al ( , 2013 concluded that the dominant species, P. pinaster, had a predominantly high rate of natural regeneration. Mean seedling height showed a significant increase in time (5 years) at the study area from 1.7 to 49.5 cm.…”
Section: ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg ⎧(Sgv) Hg mentioning
confidence: 69%
“…The observed increase in wildfires has a drastic impact on biological productivity and composition of Mediterranean ecosystems (Calvo et al, 2003(Calvo et al, , 2005. However the effects of fire on ecosystems are very complex since they depend on fire regimes and characteristics (Naveh, 1995) as well as on the response of vegetation to such regimes and on environmental factors (De Luís et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Fire creates open areas, which favour the germination of species by removing established vegetation, and also has direct effects on germination and seedling survival (Hanley and Fenner 1998). The passage of fire may facilitate germination and the development of several species by changing the mineral nutrient content of the environment (Marcos 1997;Calvo et al 2003Calvo et al , 2005. Trends in secondary succession beginning after a fire depend on several factors, including species composition in the initial community, fire severity, the season in which burning occurs (Dominguez et al 2002) and the existence of either a soil or aerial seed bank able to survive disturbances (Ferrandis et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, competitive effects on the establishment of P. pinaster seedlings can also be expected in forests where the dominant understorey species consist mostly of woody and herbaceous resprouters (Calvo et al 2003). Several studies have highlighted rapid post-fire regeneration in resprouter species such as Erica australis (Willk.…”
Section: Introductionmentioning
confidence: 99%